Peningkatan pemahaman guru dalam mengembangkan pembelajaran sosial emosional sebagai aktualisasi program pendidikan guru penggerak bagi guru sd - Sukarno, Sukarno; Marmoah, Sri; Supianto, Supianto; Zuhro, Nurul Shofiatun (Jurnal Pendidikan Dasar, 2022)
Abstract. The purpose of this study was to determine the increase in the understanding of elementary school teachers in developing SEL through training and mentoring methods with work visits. This research is a quantitative descriptive study with a one-group pretest-posttest research design. The sample in this study were teachers in Ngawi Regency, East Java Province. The data collection technique used is a test. Data were analyzed using N-Gain. The results showed an increase in teacher understanding in developing SEL. The pre-test showed an average score of 58.60 while the post-test increased with an average score of 81.40 with N gain 2 in the High category. Thus, teachers can improve their pedagogical skills in developing SEL...